«Вся Ввласть сонетам». Деконструкция языка идеологии в творчестве Вагрича Бахчаняна - Tyszkowska-Kasprzak, Elżbieta (Przegląd Rusycystyczny, 2016)
«Сała władza dla sonetów». Dekonstrukcja języka ideologii w twórczości Wagricza Bachczaniana wagricz bachczanian, tworzący w nurcie konceptualizmu, w wielu utworach i pra-cach plastycznych wykpiwa oficjalną ideologię socjalistyczną, wykorzystując formuły nowomowy i obrazy propagandy. w tych soc-artowskich pracach burzy mity polityczne, np. mit lenina, oraz slogany nowomowy i symbole socjalistycznej agitacji. w wierszach, zaburzając pole znaczeniowe słów, podaje w wątpliwość jednoznaczną ocenę i wartość, którą narzuca język totalitarny. w rysunkach i kolażach zestawia obrazy z różnych sfer komunikacji. komiczny efekt tych zabiegów prowadzi do degradacji propagandowych haseł, mitów i idei. «All power for sonets» Deconstruction of the language of ideology in the works by Vagrich Bakhchanyan Vagrich bakhchanyan, creating in the stream of conceptualism, in his literature and painting ridicules official socialist ideology, using the formula of newspeak and pro-paganda images. in these sots art works he destroys various political myths, eg. the myth of lenin, and so called newspeak slogans and symbols using by socialist agi-tation. in his poetry bakhchanyan shatters the semantic field of words, he doubts that totalitarian language has its clear and inambiguous meaning. in his images and collages he composes together different spheres of communication. the comic effect of these treatments leads to the degradation of the propaganda slogans, myths and ideas.